2012
DOI: 10.1515/shll-2012-1129
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Acquisition of Spanish Voiced Stop Spirantization during an Extended Stay Abroad

Abstract: The purpose of the current study is to investigate the acquisition of spirantization of /b, d, ɡ/ in the Spanish of adult learners who have spent two years abroad in a Spanish-speaking country. In addition to whether or not participants acquired spirantization, this study seeks to discover the influence of certain factors (e.g. style, prior Spanish instruction, Spanish language use, attitude, motivational intensity, etc.) on their target-like pronunciation of /b, d, ɡ/. Two different tasks were administered, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 30 publications
7
26
0
Order By: Relevance
“…Similarly, Alvord and Christiansen (2012) observed that students who had lived abroad for an extended period of time exhibit much better pronunciation ofthe Spanish spirants [ß, Ô, y] than those who have not been abroad. Face and Menke (2009) and Menke and Face (2010) also found that very advanced students who had been abroad produced more Spanish-like vowels and consonants than less advanced students who had not spent time abroad.…”
Section: Pronunciation In Language Classrooms and Study Abroadmentioning
confidence: 97%
“…Similarly, Alvord and Christiansen (2012) observed that students who had lived abroad for an extended period of time exhibit much better pronunciation ofthe Spanish spirants [ß, Ô, y] than those who have not been abroad. Face and Menke (2009) and Menke and Face (2010) also found that very advanced students who had been abroad produced more Spanish-like vowels and consonants than less advanced students who had not spent time abroad.…”
Section: Pronunciation In Language Classrooms and Study Abroadmentioning
confidence: 97%
“…Because L2 speakers face little communicative pressure to acquire this type of target sound, acquisition may depend on a broader array of factors, including individual differences in motivation, willingness to communicate, and other personal characteristics. In that regard, Alvord and Christiansen (2012) and Rogers and Alvord (2014) reported that factors such as motivation and language use predicted advanced Spanish learners' spirantization of /b, d, g/.…”
Section: Discussionmentioning
confidence: 99%
“…It could be argued that scripted tasks combine a focus on form with orthography, whereas interview tasks are more communicative in nature and avoid orthographic effects. To that point, Alvord and Christiansen (2012) found that participants did not produce significantly different rates of approximantization on two scripted tasks, a word list and short story reading. Given that Spanish and English make use of the same graphemes but do not map them to underlying forms in the same way, it seems likely that taks involving orthography induce learners to produce more stop-like variants.…”
Section: Second Language Acquisition Of Spanish Approximantsmentioning
confidence: 96%
See 1 more Smart Citation
“…L2 pronunciation learning is no exception. For instance, the learning of various linguistic dimensions of L2 speech has been linked to learners' age , the quantity and quality of their contact with the L2 (Moyer, 2011), their motivation and cultural sensitivity (Alvord & Christiansen, 2012;BakerSmemoe et al, 2014;Hardison, 2014), and their willingness to communicate (Baran-Łucarz, 2014;. These findings clearly argue against a 'one-size-fits-all' approach to pronunciation teaching and assessment, suggesting that different learners can respond differently to the same testing materials and procedures, and that different materials and procedures might be necessary for assessment of diverse populations of learners.…”
Section: A Focus On Individual Differencesmentioning
confidence: 99%